The Effectiveness of Animated Video as Learning Media Towards The Perception of Healthy Snacks on Elementary School Students in Indonesia - Mutia Yusuf; Zuhrawardi Zuhrawardi; Elly Wardani (The Faculty of Veterinary Medicine of Syiah Kuala University, 2020)
The negative effect of consuming unhealthy snacks is foodborne illness caused by food and drinks that have been contaminated with germs. This problems need a serius intervention especially education for the school children to develop understanding of the importance of healthy, safe and nutritious snacks. It was reported that 73% of elementary school students have low knowledge and 81% have low attitude towards healthy snacks. Amongst efforts to educate children on healthy snacks is the audio-visual media. This study is conducted to investigate the effectiveness of animated video and power point as learning media towards the perception of healthy snacks on elementary school students in Indonesia. The design is quasi experiment with control group, with the sample of grade 5s' elementary school students. Data were collected using questionnaires developed from health belief model and intervention is given in the form of health education using animated video media. The results show that there are perception differences in susceptibility (P=0.0001), seriousness (P=0.0001), benefits (P=0.0001), and obstacles (P=0.0001) related to healthy snacks before and after education with animated video. Based on that, it is expected to the schools and parents to give attention to the quality of the snacks by educating and providing the children with healthy snack options.